Incorporating a rainfall intensity modification factor γ into the I a - S Relationship in the NRCS-CN method - Hu, Pengcheng; Tang, Jialiang; Fan, Jihui; Shu, Shumiao; Hu, Zhaoyong; Zhu, Bo (International Soil and Water Conservation Research, 2020)
The Natural Resources Conservation Service runoff curve number (NRCS-CN) method is widely used to simulate direct runoff, but the impact of rainfall intensity has not been considered. In this study, a rainfall intensity modification factor (γ) was incorporated into the Ia-S relationship of the NRCS-CN method, and the modified method (NRCS-CN-γ) was compared with the NRCS-CN method withλ=0.2 andλ=0.05 in three watersheds of the Walnut Gulch Experimental Watershed (WGEW). The results showed that for 2016-2018 period, the simulation performance of the NRCS-CN-γ method was close to the NRCS-CN (λ = 0.05) method and better than the NRCS-CN (λ = 0.2) method. When the new data (2009 data with high variance) was added, the significant improvement was observed by NRCS-CN-γmethod with all the evaluation parameters being the best in the three watersheds, indicating a more adapted capa-bility of the modified method with highly uneven rainfall intensities. The covariance between rainfall intensity and the simulated runoff were 19.01, 15.14, and 16.35 for the three methods, respectively. When the optimal CN changed, the relative errors representing CN sensitivity were 6.25, 6.49 and 17.39 for the methods, respectively. It is suggested that the NRCS-CN-γ method outperformed the other two methods and could contribute to a more accurate estimation of direct runoff where rainfall intensity greatly varied, especially in monsoon region or under the context of climate change.